2020
DOI: 10.1101/2020.12.01.20242123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral Inhibition and Dual Mechanisms of Anxiety Risk: Disentangling Neural Correlates of Proactive and Reactive Control

Abstract: Background: Behavioral inhibition (BI) is a temperament style characterized by heightened reactivity and negative affect in response to novel people and situations, and it is a strong predictor of anxiety problems later in life. However, not all BI children develop anxiety problems and mounting evidence suggests that how one manages their cognitive resources (cognitive control) influences anxiety risk. The present study tests whether more (proactive control) or less (reactive control) planful cognitive strateg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In contrast to behavioral measures, neural measures permit characterization of activity during the individual cue-locked and probe-locked time windows and thus may provide more specific measures of control processes. Valadez et al (2021) examined ERPs drawn from EEG data that were simultaneously collected during the 15-year administration of the AX-CPT. Using separate cue-and probe-locked ERPs, they found that BI was associated with anxiety only among youth who tended not to differentiate between cues during the earlier cue period (indicating a less proactive strategy) but instead differentiated between them during the later probe period (indicating a more reactive strategy).…”
Section: The Ax Continuous Performance Testmentioning
confidence: 99%
“…In contrast to behavioral measures, neural measures permit characterization of activity during the individual cue-locked and probe-locked time windows and thus may provide more specific measures of control processes. Valadez et al (2021) examined ERPs drawn from EEG data that were simultaneously collected during the 15-year administration of the AX-CPT. Using separate cue-and probe-locked ERPs, they found that BI was associated with anxiety only among youth who tended not to differentiate between cues during the earlier cue period (indicating a less proactive strategy) but instead differentiated between them during the later probe period (indicating a more reactive strategy).…”
Section: The Ax Continuous Performance Testmentioning
confidence: 99%